2005
DOI: 10.1099/jmm.0.45853-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of three different ELISA methods for the diagnosis of early culture-confirmed Lyme disease in Italy

Abstract: In this study the raising and development of the immune response to Borrelia burgdorferi infection in 45 Italian patients suffering from culture-confirmed Lyme borreliosis erythema migrans was investigated. A total of 95 serially collected serum samples were tested by using three different commercial ELISAs: recomWell Borrelia (Mikrogen), Enzygnost Borreliosis (DADE Behring) and Quick ELISA C6 Borrelia (Immunetics). The sensitivities of the ELISAs were as follows: Enzygnost Borreliosis IgM, 70 . 5 %; Quick ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
(40 reference statements)
0
15
1
2
Order By: Relevance
“…Over the past few years, the C6 test has come to the fore of Lyme disease diagnosis, either as a single test or in combination with other assays, such as immunoblotting (2,(8)(9)(10). To date, the remaining IRs and invariable domains have not been explored completely for their general antigenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, the C6 test has come to the fore of Lyme disease diagnosis, either as a single test or in combination with other assays, such as immunoblotting (2,(8)(9)(10). To date, the remaining IRs and invariable domains have not been explored completely for their general antigenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The C6 assay has become the assay of choice both in the United States and Europe, either alone (3,6,8,9,14,17) or in combination with other assays (1,4,12). Sensitivity of this assay in Europe varies between 91% in a study in The Netherlands against a panel of sera from clinically defined Lyme patients confirmed by immunoblotting (16) and 33% in Italy against a panel of sera from clinically defined Lyme patients with EM confirmed by culture (10).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, a few papers on the diagnostic use of the C6 peptide have been published (9,14,16,22,23). Moreover, Bacon and coworkers (2) reported that the test with the C6 peptide performed as well as or better than the two-tiered algorithm.…”
mentioning
confidence: 99%